Social identity and intergroup relations - Jelić, Margareta; Ajduković, Dean (2005)
The objective of this study was to explore the impact of social identity, personal and social self-esteem on in-group bias and outgroup discrimination. We hypothesised that majority group members would have higher social identity and social self-esteem and would therefore show higher tendency towards in-group bias as well as towards outgroup discrimination. The relationship between the mentioned variables in everyday setting was investigated on two conflicted ethnic groups. The sample consisted of 1039 adults living in the city of Vukovar, Croatia. Half of the participants were members of the majority group and half of the minority group. Results indicate that ethnic identity level and social self-esteem are important when investigating intergroup processes. Minority or majority group membership proved to be the most important factor for expressing in-group bias and outgroup derogation. Members of majority and minority groups differ in all variables. In line with research done in this area, members of the majority group show higher social self-esteem and scored higher on ethnic identity and also tend to express more in-group bias and outgroup derogation than members of the minority group. The importance of environmental and political context for investigating group processes is emphasized.
Projekt MZOS
ENG